Efficient fixation of CO2 into carbonates by tertiary N-functionalized poly(ionic liquids): Experimental-theoretical investigation. Issue 44 (February 2021) - He, Yuting; Jiang, Ding; Li, Xue; Ding, Jing; Li, Hongping; Wan, Hui; Guan, Guofeng
Graphical abstract: The multi-step conversion of CO2 greatly enriches the diversity of products, and provides more possibilities of developing green synthetic processes for chemical intermediates in fine chemistry. However, the multi-step reaction of CO2 puts forward more stringent requirements for the multifunctional design of catalysts. In this work, the prominent performance was achieved by bifunctional poly(ionic liquid)s via in situ polymerization of hydroxy ionic liquids and 1-vinylimidazole, which can accelerate both the CO2 cycloaddition and the transesterification to form dimethyl carbonate (DMC) without solvent or co-catalyst. The DFT calculation reasonably explained the multi-site activation of hydroxyls promoting polarization of epoxides, halogen anions inducing epoxides ring-opening, and tertiary N of 1-vinylimidazole facilitating CO2 activation and subsequent dissociation of methanol. Highlights: Novel ternary copolymerized bifunctional poly(ionic liquid)s (TBPILs) are successfully fabricated. With the help of tertiary N, TBPILs can accelerate both the CO2 cycloaddition and subsequent transesterification. The specific activity of TBPILs is 17.87 mmolSC·m −2 catal ·h −1 in CO2 cycloaddition reaction. The yield of DMC reaches up to 80.31 % without any solvent or co-catalyst. DFT calculations, combined with ESP and ALIE analyses, detailed illustrate the dual roles of tertiary N in the formation of carbonates. Abstract: The efficiency and versatility of catalysts in the multi-step reaction of carbonates with carbon dioxide (CO2 ) as raw material are barely satisfactory. Herein, ternary copolymerized bifunctional poly(ionic liquid)s (TBPILs) rich in hydroxyls, halogen anions and tertiary N were fabricated via free radical copolymerization. Due to the ingenious modification of tertiary N in the polymeric framework to form multi-site activation with hydroxyls and halogen anions, the specific activity of TBPILs reached to 17.87 mmolSC m −2 catal h −1 in CO2 cycloaddition reaction. Meanwhile, for the transesterification reaction of cyclic carbonates with methanol, by the introduction of tertiary N, the yield of dimethyl carbonate increased from trace to 80.31 % in the absence of any solvent or co-catalyst. Density functional theory calculations, combined with electrostatic potential and average local ionization energy analyses confirmed the dual roles of tertiary N in the formation of carbonates by CO2 . This work provides an originality idea to design high-efficiency catalysts for CO2 insertion into carbonates, and study the effects of basic sites on CO2 conversion.